2011
DOI: 10.1126/science.1199214
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Factor Progranulin Binds to TNF Receptors and Is Therapeutic Against Inflammatory Arthritis in Mice

Abstract: The growth factor progranulin (PGRN) has been implicated in embryonic development, tissue repair, tumorigenesis, and inflammation, but its receptors remain unidentified. We report that PGRN bound directly to tumor necrosis factor receptors (TNFR), and disturbed the TNFα/TNFR interaction. PGRN-deficient mice were susceptible to collagen-induced arthritis, and administration of PGRN reversed inflammatory arthritis. Atsttrin, an engineered protein composed of three PGRN fragments, exhibited selective TNFR binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
983
8
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(1,037 citation statements)
references
References 36 publications
43
983
8
3
Order By: Relevance
“…In contrast to TNFa, Atsttrin exhibited a higher binding affinity for TNFR2, but a lower affinity for TNFR1. 29 In addition, it was also observed that TNF family ligands bind to the extracellular regions of TNFR1 and TNFR2 in which each receptor subunit contacts 2 adjacent ligand subunits typically via CRD2 and CRD3(cysteine-rich repeat domains, CRDs). 51,60 Deletion mutants of TNFR1 and TNFR2 used to map the binding of PGRN revealed that CRD2 and CRD3 of TNFR are essential for the interaction with PGRN, similar to the binding to TNFa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to TNFa, Atsttrin exhibited a higher binding affinity for TNFR2, but a lower affinity for TNFR1. 29 In addition, it was also observed that TNF family ligands bind to the extracellular regions of TNFR1 and TNFR2 in which each receptor subunit contacts 2 adjacent ligand subunits typically via CRD2 and CRD3(cysteine-rich repeat domains, CRDs). 51,60 Deletion mutants of TNFR1 and TNFR2 used to map the binding of PGRN revealed that CRD2 and CRD3 of TNFR are essential for the interaction with PGRN, similar to the binding to TNFa.…”
Section: Discussionmentioning
confidence: 99%
“…51 Recently, it has been shown that PGRN binds to TNFR, interfering with the interaction between TNFa and TNFR. 29 However, the possibility that TNFR could be a specific receptor for PGRN-mediated effects in insulin resistance has never been tested, and it is still hard to clearly define the early stages of PGRN-mediated signaling from the plasma membrane. TNFR1 and TNFR2 do not share homology in the cytoplasmic domains but exhibit a low degree of similarity, which suggests that they are capable of inducing distinct cellular responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progranulin is a 593 amino acid glycoprotein consisting of 7.5 tandem repeats of a 12-cysteine granulin motif. Although its function is only incompletely understood, progranulin may be a physiological antagonist of tumor necrosis a signaling (Tang et al 2011). It has been reported to act on nerve cells by binding to sortilin following release from activated microglial cells (Hu et al 2010).…”
Section: Mutations In Grnmentioning
confidence: 99%
“…Progranulin deficiency in mice leads to elevated neuro-inflammation, frontotemporal dementia [24][25][26], resulting in inflammation and progression of collagen-induced arthritis [27][28]. Progranulin has been also found in human blood and urine [28][29][30][31][32][33]. It has been recently used as a chronic inflamemation marker in obesity and type 2 diabetes mellitus [34].…”
Section: Introductionmentioning
confidence: 99%